math.com
Home    |    Teacher    |    Parents    |    Glossary    |    About Us
Homework Help Practice Ask An Expert Calculators & Tools Games Store
Email this page to a friend Email this page to a friend
Resources
· Cool Tools
· Formulas & Tables
· References
· Test Preparation
· Study Tips
· Wonders of Math
 
Search
Custom Search



Math Jobs


  
Derivadas hiperbolicas
(Matemática | Cálculo | Derivadas | Tabla de | Hiperbolicas)

Demostraciones de las derivadas de los hiperbolicas.

d/dx sinh(x) = cosh(x)
d/dx cosh(x) = sinh(x)
d/dx tanh(x) = 1 - tanh(x)2
d/dx csch(x) = -coth(x)csch(x)
d/dx sech(x) = -tanh(x)sech(x)
d/dx coth(x) = 1 - coth(x)2


Demostración de (d/dx)sinh(x) = cosh(x) : Desde la derivada de ex

Dando: sinh(x) = ( ex - e-x )/2; cosh(x) = (ex + e-x)/2; (d/dx) ( f(x)+g(x) ) =(d/dx) f(x) + (d/dx) g(x); La regla de la cadena; (d/dx)( c*f(x) ) = c (d/dx)f(x).
Resuelva:

(d/dx) sinh(x)= (d/dx) ( ex- e-x )/2 = 1/2 (d/dx)(ex) -1/2 (d/dx)(e-x)
= 1/2 ex + 1/2 e-x = ( ex + e-x )/2 = cosh(x)       Q.E.D

Demostración de (d/dx)cosh(x) = sinh(x) : Desde la derivada de ex

Given: sinh(x) = ( ex - e-x )/2; cosh(x) = (ex + e-x)/2; (d/dx) ( f(x)+g(x) ) =(d/dx) f(x) +(d/dx) g(x); La regla de la cadena; (d/dx)( c*f(x) ) = c (d/dx)f(x).
Resuelva:

(d/dx) cosh(x)= (d/dx) ( ex + e-x)/2 = 1/2 (d/dx)(ex) + 1/2 (d/dx)(e-x)
= 1/2 ex - 1/2 e-x = ( ex - e-x )/2 = sinh(x)       Q.E.D.

Demostración de (d/dx) tanh(x)= 1 - tan2(x) : desde las derivadas de sinh(x) y cosh(x)

Dando: (d/dx)sinh(x) = cosh(x); (d/dx)cosh(x) = sinh(x); tanh(x) = sinh(x)/cosh(x); La Regla de Cocientes.
Resuelva:

(d/dx) tanh(x)= (d/dx) sinh(x)/cosh(x)
= ( cosh(x) (d/dx)sinh(x) - sinh(x) (d/dx)cosh(x) ) / cosh2(x)
= ( cosh(x) cosh(x) - sinh(x) sinh(x) ) / cosh2(x) = 1 - tanh2(x)       Q.E.D.

Demostración de (d/dx) csch(x)= -coth(x)csch(x), (d/dx)sech(x) = -tanh(x)sech(x), (d/dx)coth(x) = 1 - coth2(x) : Desde las derivadadas de sus funciones recíprocas

Dando: (d/dx)sinh(x) = cosh(x); (d/dx)cosh(x) = sinh(x); (d/dx)tanh(x) = 1 - tanh2(x); csch(x) = 1/sinh(x); sech(x) = 1/cosh(x); coth(x) = 1/tanh(x); La Regla de Cocientes.

(d/dx) csch(x)= (d/dx) 1/sinh(x)= ( sinh(x) (d/dx)1 - 1 (d/dx) sinh(x))/sinh2(x) = -cosh(x)/sinh2(x) = -coth(x)csch(x)
(d/dx) sech(x)= (d/dx) 1/cosh(x)= ( cosh(x) (d/dx)1 - 1 (d/dx) cosh(x))/cosh2(x) = -sinh(x)/cosh2(x) = -tanh(x)sech(x)
(d/dx) coth(x)= (d/dx) 1/tanh(x)= ( tanh(x) (d/dx)1 - 1 (d/dx) tanh(x))/tanh2(x) = (tanh2(x) - 1)/tanh2(x) = 1 - coth2(x)

  
 
  

 
Contact us | Advertising & Sponsorship | Partnership | Link to us

© 2000-2005 Math.com. All rights reserved.     Legal Notices.     Please read our Privacy Policy.